Green Product Innovation Increase Competitive Advantage, Mediated by Green Dynamic Capability - Fatiha, Kirana Shaadah; Linda, Muthia Roza (Journal of Management and Administration Provision, 2025)
This study examines how Padang City's bakery MSMEs' competitive advantage is impacted by green product innovation and green dynamic capabilities.  This research employs a quantitative methodology.  210 MSME actors were given questionnaires to complete in order to collect data. The surveys were subsequently processed using SmartPLS 4.0 software, yielding the following findings:  1) Competitive Advantage is positively and significantly impacted by Green Product Innovation; 2) Green Product Innovation is positively and significantly impacted by Green Dynamic Capability; 3) Green Dynamic Capability is positively and significantly impacted by Competitive Advantage; and 4) Green Dynamic Capability positively and significantly mediates the effect of Green Product Innovation on Competitive Advantage.